Mg2+-dependent ATPase activity in Malpighian tubules of Triatoma infestans Klug - Vilela de Azeredo-Oliveira, Maria Tercilia [UNESP]; da Silva, Tiago Lucena [UNESP]; Silveira Mello, Maria Luiza (Pergamon-Elsevier B.V. Ltd, 2012)
Mg2+-dependent ATPases were investigated in Malpighian tubules of the blood-sucking insect, Triatoma infestans, with cytochemical procedures for light and electron microscopy. The aim was to establish patterns of enzyme occurrence in the blood-sucking insect under control rearing conditions for further comparisons with animals subjected to the action of stress factors. Enzyme activity was found in laminated "concretions" present in distal cells, in edges of urate crystals at the lumen of the proximal region of tubules, in the basement membrane of proximal cells, and variously distributed in plasmalemma invaginations of both distal and proximal cells. Presence of ATPases in the "concretions" and urate crystals is presumed to be due to engulfment of other ATPase-containing components during formation of these structures. Cytochemical reactivity in the basement membrane and plasmalemma invaginations is assumed to be involved with active transport of waste molecules from and to hemolymph and differs as a function of the Malpighian tubule region. This paper provides a basic understanding of the enzyme occurrence in the blood sucking insects, and can be used as a pattern for comparative means of the staining patterns among Triatominae species. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Mg2+-dependent ATPase; Malpighian tubules; Triatoma infestans; Cytochemistry